The drum in the mosque; A modern short story by Djajus Pete - Quinn, George (UI Scholars Hub, 2021)
The short story “Bedhug” (The drum in the mosque) by Djajus Pete (born 1948) was first published in the Javanese-language magazine Panjebar Semangat in 1997. It describes what happens in a small village when well-intentioned local people unsuccessfully attempt to replace an old mosque drum with a bigger, more resonant one. In many Muslim communities, the call to prayer is made by beating a drum in the mosque’s vestibule. The story gives a glimpse of how Islam is changing, and not changing, in Java. It is critical of village institutions and functionaries, but also humorous and deeply affectionate.